High Density Polyethylene/Pistachio Shell Flour/Nanoclay Composites - Effect of Accelerated Weathering Conditions on Mechanical Properties, Relative Brightness and Total Colour Change. Issue 4 (May 2017) - Najafabadi, M.A. Abedini; Khorasani, S. Nouri; Esfahani, J. Moftakharian
This study investigates the effect of the addition of nanoclay (Cloisite 20A) on some mechanical properties, % relative brightness (ΔLrel ) and total colour change (ΔEab ) of high density polyethylene (HDPE)/pistachio shell flour (PSF) composites when exposed to accelerated weathering conditions. X-ray diffraction (XRD) patterns of samples containing 3 and 6 per hundred composite (phc) of nanoclay indicated partial exfoliation and intercalation. The tensile modulus and tensile strength of HDPE/PSF composites (without nanoclay) decreased when the exposure time increased to 1500 h, while the tensile modulus and tensile strength increased. For samples with nanoclay, ΔLrel and ΔEab increased upon accelerated weathering conditions up to 500 h, and thereafter remained constant. But results show that ΔLrel and ΔEab increased significantly upon accelerated weathering exposure in HDPE/PSF samples up to 1500 h. Scanning electron microscopy (SEM) results after 1500 h exposure to weathering condition showed signs of the presence of cracks in samples without nanoclay, unlike the samples with nanoclay.